Exploring Cultural Identity of Senior High School Students through Digital Storytelling “Lutung Kasarung “as Sundanese Folklore - Friatin, Lilies Youlia (Yayasan Literasi Sains Indonesia, 2023)
This qualitative research explores the impact of digital storytelling on the cultural identity exploration of Senior High School students using the Sundanese folklore